2020
DOI: 10.3390/ani10091534
|View full text |Cite
|
Sign up to set email alerts
|

Udder Morphometry and Its Relationship with Intramammary Infections and Somatic Cell Count in Serrana Goats

Abstract: The external morphological traits of the mammary gland, and their relationships with somatic cell count (SCC) and the presence of intramammary infection (IMI), were studied in 30 Serrana goats, Transmontano ecotype. Globular-shaped udders were the most predominant, with slightly separated and symmetrical halves, presenting some degree of suspension. Funnel-shaped teats were the most prevalent shape with an opening of 120° to 160° degrees. Significant differences were observed between healthy group and the coag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Margatho et al . (2020) also reported that udder characteristics significantly affect the number of SCC and microorganisms, and bifurcated pendular udders, where teats are vertically loose and very close to each other, are more prone to intramammary infections. Therefore, it can be predicted that a flat udder shape and then the defined halving shape will be more suitable for pasture, milking and milk quality.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Margatho et al . (2020) also reported that udder characteristics significantly affect the number of SCC and microorganisms, and bifurcated pendular udders, where teats are vertically loose and very close to each other, are more prone to intramammary infections. Therefore, it can be predicted that a flat udder shape and then the defined halving shape will be more suitable for pasture, milking and milk quality.…”
Section: Discussionmentioning
confidence: 97%
“…In general, it was seen that the positive relationship between udder characteristics and lactation yield were significant. These results agree with several other studies in both goat and sheep breeds (Mavrogenis et al ., 1988; Emediato et al ., 2008; Margatho et al ., 2020). Margatho et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria are also transported passively by liners. However, the intra mammary infections (IMI) prevalence's do not seem to be signi cantly different between dairy (hand or machine milked) and meat ocks [59]. Transmission is also possible by "milk-robber" lambs (buccal carriage) and may be important for staphylococci, Pasteurellaceae, parapoxvirus (contagious ecthyma) [60].…”
Section: Transmissionmentioning
confidence: 99%
“…2. According to Margatho et al (2020), Serrana goats can have a pear-shaped or pendular cylindrical udder, but the most prominent shape is globular as described by ANCRAS (2020). The udder perimeter is 31.3 ± 9.1 cm, the udder cleft 21.6 ± 8.0 cm and the udder depth 6.4 ± 4.0 cm.…”
Section: Serrana Breed Standardsmentioning
confidence: 99%